Sosialisasi Pemanfaatan Potensi Unggulan Hasil Pertanian Singkong Menjadi Tepung Mocaf (Modified Cassava Flour) Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Di Kelurahan Balai Raja Kecamatan Pinggir Kabupaten Bengkalis - Wahyu Ainurrahmansyah; Salsa Nabila Mailani; Ajeng Eka Dianti Ningsih; Nurul Mahfira Tunisa; Fitra Andwika; Annisa Meliana; Zidan Fajar Ramadhan; Aziva Iftinah; Dina Amalia Fithri (FKIP, Universitas Palangka Raya, 2023)
Balai Raja Village, Pinggir District, Bengkalis Regency has potential from the agricultural sector, namely cassava, which can improve the welfare of the local community. Cassava is a leading commodity because almost half of the population of this sub-district are cassava farmers. However, the obstacle is that the utilization of cassava harvests is not yet optimal due to the lack of public knowledge in diversifying cassava processing. As an implementation of the Tri Dharma of Higher Education, namely community service, we carry out outreach in the form of processing cassava into mocaf in an effort to utilize the superior potential of the local area. The socialization we carried out used the Participatory Rural Appraissal method by delivering an explanatory presentation about mocaf and a demonstration of mocaf processing using the Bimo-CF enzyme. The people who attended were very enthusiastic in welcoming this activity so we hope that the mocaf development process can be produced sustainably